Environmental Enrichment of Pigs - Romans, Emma F (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Pigs have a strong motivation to explore and root. In conventional pig husbandry systems, this need is difficult to fulfil, unless adequate enrichment materials are provided. This book summarises how enrichment strategies for pigs have evolved over the last few decades in different countries and provides a vast array of possibilities to enhance the exploratory needs of pigs. The role of enrichment material on avoidance of tail biting outbreaks or as an element triggering positive emotions in pigs is also discussed.